THE EFFECTIVENESS OF MEMORIZATION TECHNIQUES IN ENGLISH LEARNING AT AL IHSAN ISLAMIC BOARDING SCHOOL - Izzah, ikhsanul; Ridho, Muhammad Hayat; Eko, Eko (JR-ELT (Journal of Research in English Language Teaching), 2024)
This study aims to explore the effectiveness and obstacles of the memorization method in English learning at Al Ihsan Islamic Boarding School. Using a descriptive qualitative approach, data were collected through in-depth interviews with a grade 12 student selected by purposive sampling. The results showed that the memorization method has significant advantages in helping students master vocabulary and build learning discipline. Memorization is an effective tool for remembering new vocabulary consistently, which provides a strong foundation for students in understanding texts and other learning materials. In addition, the memorization routine helps students form structured learning habits. However, this study also revealed several obstacles, including a lack of contextual understanding of the memorized vocabulary, boredom due to repetition, time constraints due to the busy schedule of the Islamic boarding school, and teaching materials that do not support contextualization. To overcome these obstacles, the integration of the memorization method with a context-based approach and more interactive activities is needed. The use of technology and variations in teaching methods can also increase student motivation and understanding. This study confirms that the memorization method remains relevant in English learning, especially in the Islamic boarding school environment. With adjustments and innovations, this method can be optimized to create more effective, interesting, and meaningful learning. The results of this study provide practical recommendations for teachers and educational institutions in developing learning strategies that suit students' needs.